Simulasi Graphical User Interface Analisis Termodinamika Mesin Turboprop Menggunakan Perangkat Lunak Matlab R2020a - Bismil Rabeta; Mohammad A.F Ulhaq; Aswan Tajuddin; Agus Sugiharto (FTK UNSURYA, 2021)
A turboprop engine is a hybrid engine that delivers thrust or jet thrust and also drives the propeller. This is basically similar to a turbojet except the turbine works through the main shaft which is connected to the reduction gear to rotate the propeller in front of the engine. This research was conducted to determine the development of engine performance in thermodynamic analysis so as to know the value of each parameter on a engine that has been developing for 20 to 50 years with different engine manufacturing. So that in this study a comparison of the thermodynamic analysis of the TPE-331, PT6A-42 and H85-200 engines was carried out. In the TPE331-10, PT6A-42, and H85-200 turboprop engines the value of fuel to air ratio and shaft work increases with increasing altitude while compressor work, fuel flow rate, shaft power, propeller thrust, jet thrust, total thrust, equivalent engine power and ESFC decrease with increasing altitude. Furthermore, the turbine's working value is relatively stable as the altitude increases. After that, the value of compressor work and turbine work on the PT6A-42 engine was greater than that of the TPE331-10, and H85-200 engines. However, the value of the fuel to air ratio, fuel flow rate, shaft power, jet thrust, equivalent engine power and ESFC on the H85-200 engine was greater than the TPE331-10 and PT6A engines. Furthermore, at sea level, the value of the axle, propeller thrust, and total thrust on the H85-200 engine is greater than that of the TPE331-10 and PT6A-42 engines but at an altitude of 25,000 ft, the PT6A-4 engine has a greater value than that of the TPE331-10 and PT6A-42 engines. TPE331-10, and H85-200 engines.